Does crowd support drive the home advantage in professional soccer? Evidence from German ghost games during the Covid-19 pandemic - Fischer, K.; Haucap, J. (CESifo Working Paper, 2020)
This paper examines the relation between crowd support and home advantage in professional football in making use of a unique "natural experiment" induced by restrictions due to the Corona pandemic: so-called ghost games in the top three German football divisions during the 2019/2020 season. We find that there is a reduced home advantage in the first division, whereas no change is observed in the second and third division. Our regression analysis indicates that the decrease in the home advantage and the heterogeneity across divisions are not sensitive to a variety of performance, location, and team covariates and best explained by the lower occupancy rate in the stadia. Hence, the decrease in occupancy to zero at the ghost games has been less dramatic for teams that have been used to low occupancy rates. The ghost game effect decreases over time, however, implying that players adapt and get used to the new situation. We cannot find strong evidence for a change in referee behavior or teams' tactics as main impact channels of occupancy rates on the home advantage. We rather assess psychological reasons to be of higher importance.